Dynamics of history-dependent perceptual judgment - Hachen, I.; Reinartz, S.; Brasselet, R.; Stroligo, A.; Diamond, M. E. (Nature communications, 2021)
Identical physical inputs do not always evoke identical percepts. To investigate the role of stimulus history in tactile perception, we designed a task in which rats had to judge each vibrissal vibration, in a long series, as strong or weak depending on its mean speed. After a low-speed stimulus (trial n − 1), rats were more likely to report the next stimulus (trial n ) as strong, and after a high-speed stimulus, they were more likely to report the next stimulus as weak, a repulsive effect that did not depend on choice or reward on trial n − 1. This effect could be tracked over several preceding trials (i.e., n − 2 and earlier) and was characterized by an exponential decay function, reflecting a trial-by-trial incorporation of sensory history. Surprisingly, the influence of trial n − 1 strengthened as the time interval between n − 1 and n grew. Human subjects receiving fingertip vibrations showed these same key findings. We are able to account for the repulsive stimulus history effect, and its detailed time scale, through a single-parameter model, wherein each new stimulus gradually updates the subject’s decision criterion. This model points to mechanisms underlying how the past affects the ongoing subjective experience. Identical physical inputs can evoke non-identical percepts. Here, the authors investigate the sources of such variability and find that rats and humans, trained to judge tactile vibration strength, express a robust sequential effect that could be modeled as the trial-by-trial incorporation of sensory history.